Fluoride release of giomer and resin based fissure sealants = Liberación de flúor de sellantes de fosas y fisuras a base de resina y/o ionómero - Şişmanoğlu, Soner (2019)
Fissure sealants are applied to teeth to prevent caries development. The presence of the fissure sealant creates a protective barrier, which prevents plaque accumulation to the pits and fissure. They have a significant role in preventing pit and fissure caries. The aim of this study was to evaluate the time-dependent fluoride ion release of giomer- and resin-based fissure sealants. Fissure sealants were divided into 4 groups: BeautiSealant (Shofu, Japan), Clinpro Sealant (3M ESPE, USA), Helioseal F (Ivoclar Vivadent, Liechtenstein), Fissurit F (Voco, Germany). Disk shaped samples were prepared for each sealant material tested, and they were transferred into polyethylene vials containing 5 ml of deionized water. Fluoride ion diffusion was determined on days 1,2,3,7,14,21, and 28 (n=7). The fluoride concentration in these samples was analyzed using a pre-calibrated spectrophotometer in parts per million (ppm). These experiments were performed in triplicates at room temperature. ANOVA and Tukey's HSD test were used for statistical analysis. BeautiSealant was released the highest amount of fluoride on day 1 (5.33 ppm), followed by a sudden decrease on the day 2 (2.17ppm). The burst effect was observed only in this group. Clinpro Sealant, Fissurit F and HelioSeal F groups presented fluoride release of 2.69, 2.94 and 2.91 ppm on the first day, respectively, without a significant difference (p>0.05). After the first week, a constant fluoride release level has been reached. The fluoride release for the three resin-based fissure sealants was slightly lower than that for the giomer-based. After the first week, materials exhibited no significant difference and reached a plateau. The usage of a high and prolonged fluoride-releasing fissure sealant material should be considered by clinicians, particularly in patients with caries risk.
Los sellantes de fosas y fisuras se utilizan con el objetivo de prevenir el desarrollo de caries. La presencia del sellante crea una barrera protectora, que evita la acumulación de placa en las fosas y fisuras. Tienen un papel importante en la prevención de la caries. El objetivo de este estudio fue evaluar la liberación de iones fluoruro de los sellantes de fosas y fisuras a base de Ionómeros y resinas. Los sellantes de fosas y fisuras se dividieron en 4 grupos: BeautiSealant (Shofu, Japón), Clinpro Sealant (3M ESPE, EE. UU.), Helioseal F (Ivoclar Vivadent, Liechtenstein), Fissurit F (Voco, Alemania). Se prepararon muestras en forma de disco para cada material, y se transfirieron a viales de polietileno que contenían 5 ml de agua desionizada. La difusión de iones fluoruro se determinó en los días 1,2,3,7,14,21 y 28 (n=7). La concentración de fluoruro en estas muestras se analizó utilizando un espectrofotómetro precalibrado en partes por millón (ppm). Estos experimentos se realizaron por triplicado a temperatura ambiente. ANOVA y la prueba de HSD de Tukey se utilizaron para el análisis estadístico. BeautiSealant liberó la mayor cantidad de fluoruro en el día 1 (5.33 ppm), seguido por una disminución repentina en el día 2 (2.17ppm). Los grupos Clinpro Sealant, Fissurit F y HelioSeal F presentaron una liberación de fluoruro de 2.69, 2.94 y 2.91 ppm el primer día, respectivamente, sin una diferencia significativa (p> 0.05). Posterior a la primera semana, fue alcanzado un nivel constante de liberación de fluoruro. La liberación de flúor para los tres sellantes de fosas y fisuras a base de resina fue ligeramente inferior a la de los Ionómeros. Después de la primera semana, los materiales no mostraron diferencias significativas. Los odontólogos deben considerar el uso de un material sellante de fosas y fisuras que promueva la liberación de flúor a lo largo del tiempo, especi
En revista Odóvtos, vol. 21, no. 2 (mayo-agosto 2019)
Descripción basada en el contenido visto 16 de agosto, 2024
También disponible en formato HTML y EPUB
Keywords: SELLADORES DE FOSAS Y FISURAS (ODONTOLOGIA); MATERIALES DENTALES; FLUORUROS